Evidence for a TDE origin of the radio transient Cygnus A-2. Issue 3 (16th April 2019) - de Vries, M N; Wise, M W; Nulsen, P E J; Siemiginowska, A; Rowlinson, A; Reynolds, C S
Abstract: In 2015, a radio transient named Cygnus A-2 was discovered in Cygnus A with the Very Large Array. Because of its radio brightness (ν F ν ≈ 6 × 10 39 erg s −1 ), this transient likely represents a secondary black hole in orbit around the active galactic nucleus. Using Chandra ACIS observations from 2015 to 2017, we have looked for an X-ray counterpart to Cygnus A-2. The separation of 0.42 arcsec means that Cygnus A-2 cannot be spatially resolved, but by comparing the data with simulated marx data, we put an upper limit to the 2–10 keV X-ray luminosity of Cygnus A-2 of 1 × 10 43 erg s −1 . Using the Fundamental Plane for accreting black holes, we find that our upper limit to the X-ray flux of Cygnus A-2 in 2015–2017 disfavours the interpretation of Cygnus A-2 as a steadily accreting black hole. We suggest instead that Cygnus A-2 is the radio afterglow of a tidal disruption event (TDE) and that a peak in the 2–10 keV luminosity of the nuclear region in 2013, when it was observed by Swift and NuSTAR, is X-ray emission from the TDE. A TDE could naturally explain the X-ray light curve of the nuclear region, as well as the appearance of a short-lived, fast, and ionized outflow previously detected in the 2013 NuSTAR spectrum. Both the radio and X-ray luminosities fall in between typical luminosities for 'thermal' and 'jetted' TDE types, suggesting that Cygnus A-2 would be unlike previously seen TDEs.